2017
DOI: 10.1002/mc.22748
|View full text |Cite
|
Sign up to set email alerts
|

Novel genetic variants in the P38MAPK pathway gene ZAK and susceptibility to lung cancer

Abstract: The P38MAPK pathway participates in regulating cell cycle, inflammation, development, cell death, cell differentiation, and tumorigenesis. Genetic variants of some genes in the P38MAPK pathway are reportedly associated with lung cancer risk. To substantiate this finding, we used six genome-wide association studies (GWASs) to comprehensively investigate associations of 14,904 single nucleotide polymorphisms (SNPs) in 108 genes of this pathway with lung cancer risk. We identified six significant lung cancer risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Moreover, similar results were reported by Wang et al 24 . and Feng et al 25 . Hence, the rs754466 A allele in our study increased the expression of DLG5 in whole blood, lung, and cultured fibroblasts (Figure S4).…”
Section: Resultssupporting
confidence: 92%
“…Moreover, similar results were reported by Wang et al 24 . and Feng et al 25 . Hence, the rs754466 A allele in our study increased the expression of DLG5 in whole blood, lung, and cultured fibroblasts (Figure S4).…”
Section: Resultssupporting
confidence: 92%
“…For this investigation we extracted the genotypes of 113 genomic variants (markers) assigned to 58 genes, previously associated with the risk for LC in European decent people or one of its histological subtypes through a wide variety of approaches [ 4 11 ] or proxies thereof (called LC-marker ), and 296 markers assigned to 7 genes involved in Wnt signalling and listed in Bahl et al [ 25 , 26 ] and Yilmaz et al [ 27 ] (called AhR / Wnt-marker ). Thus, we focused this analysis to genes previously investigated with respect to LC.…”
Section: Methodsmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) have identified dozens of susceptibility loci throughout the genome that are associated with the susceptibility to lung cancer or one of its histological subtypes [ 4 11 ]. Genes related to Wnt signalling, one of the key pathway regulating cell development and stemness, were not detected as being associated to LC susceptibility in individuals of European descent so far, unlike TERT (5p15.33) that was one of the first for which a robust association was observed [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) have identified dozens of susceptibility loci throughout the genome that are associated with lung cancer (LC) or one of its histological subtypes. [1][2][3][4][5][6][7][8] Genes related to Wnt signalling, one of the key pathway regulating cell development and stemness, were not detected as being associated to LC susceptibility in individuals of European descent so far, unlike TERT (5p15.33) that was one of the first for which a robust association was observed. [9] Aberrant Wnt signalling is often observed in expression profiles of many cancers, but to date no association of Wnt/Ahr genes with susceptibility to cancer of any type has been observed.…”
Section: Introductionmentioning
confidence: 94%
“…For this investigation we extracted the genotypes of 113 genomic variants (markers) assigned to 58 genes, previously robustly associated with the risk for LC or one of its histological subtypes [1][2][3][4][5][6][7][8] or proxies thereof (called LC-marker), and 296 markers assigned to 7 genes involved in Wnt signalling and listed in Bahl et al [22,23] and Yilmaz et al [24] (called AhR/Wnt-marker). Thus, we focused this analysis to genes previously investigated with respect to LC.…”
Section: Selected Markersmentioning
confidence: 99%